Study on the preparation of graphene oxide/silica/natural rubber latex composites by different processes. Issue 3 (March 2019) - Wang, Chuansheng; Chang, Tianhao; Bian, Huiguang; Zhang, Luqi
In this study, the graphene oxide/silica/natural latex composites were prepared by four different processes, including spray sputtering drying method, dry-ice–expansion predispersion method, mechanical stirring method, and traditional drying method. Compared to the other three methods, the spray sputtering method had higher physical mechanical properties and better silica dispersion in the rubber matrix. Meanwhile, the cross-linking density of vulcanizates prepared by the spray sputtering drying method is the largest. Compared with the compound prepared by mechanical stirring, the tensile strength, tear strength, and wear resistance property of the compound prepared by spray sputtering drying method increased by 13.6%, 31.5%, and 16.7%, respectively. The tensile strength, tear strength, and wear resistance property of the compound prepared by spray sputtering drying method increased by 27.2%, 43.6%, and 24.6%, respectively, than those prepared by dry mixing method.